2012
DOI: 10.1093/eurheartj/ehs434
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microembolization during early reperfusion: infarct extension, but protection by ischaemic postconditioning

Abstract: Microembolization at reperfusion augments infarct size, but postconditioning in the presence of microembolization still reduces infarct size and attenuates infarct expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…Thrombus aspiration was no confounder of the observed protection, largely excluding coronary microembolization as an important pathomechanism of no-reflow in the present study. Yet, a recent study in pigs demonstrated the extension of myocardial infarction with superimposed coronary microembolization, but protection by ischemic postconditioning from infarction was even more pronounced when there was superimposed microembolization [24]. As previously shown for hypothermia [5], the present study by Mewton et al also suggests a somewhat greater protection by ischemic postconditioning from coronary microvascular obstruction than from myocardial infarction, but still a close correlation between infarct size and size of areas with coronary microvascular obstruction.…”
supporting
confidence: 82%
“…Thrombus aspiration was no confounder of the observed protection, largely excluding coronary microembolization as an important pathomechanism of no-reflow in the present study. Yet, a recent study in pigs demonstrated the extension of myocardial infarction with superimposed coronary microembolization, but protection by ischemic postconditioning from infarction was even more pronounced when there was superimposed microembolization [24]. As previously shown for hypothermia [5], the present study by Mewton et al also suggests a somewhat greater protection by ischemic postconditioning from coronary microvascular obstruction than from myocardial infarction, but still a close correlation between infarct size and size of areas with coronary microvascular obstruction.…”
supporting
confidence: 82%
“…coronary occlusion with reperfusion 101,103,104 and impair coronary dilator reserve. 105,106 In patients, coronary microembolization is particularly seen with PCIs in saphenous vein bypass grafts, and it is here that protection devices are useful to prevent atherothrombotic debris from embolizing into the microcirculation.…”
Section: Heusch Cardioprotection and Coronary Circulation 1647mentioning
confidence: 99%
“…This maneuver has the potential to enhance thrombus dislodgement and, therefore, distal embolization, which in turn could exacerbate the final myocardial damage. 75 …”
Section: Modalities Of Reperfusion Therapymentioning
confidence: 99%
“…Despite the fact that the Ovize group never observed adverse effects with angioplasty postconditioning, it is not always technically feasible and, as discussed previously, could carry a risk of microembolization if not performed appropriately. 72,74,75,88 In contrast, the use of a safe drug as a postconditioning agent is fairly easy, provided it is available in an intravenous formulation and can be administered in a way to cover the time window for protection against lethal reperfusion injury. The Ovize group has reported that cyclosporine, administered as a single intravenous injection immediately before reperfusion, can reduce infarct size in patients with STEMI, 49,95 and Lønborg et al 96 gov: NCT01311700).…”
Section: Pharmacological Versus Ischemic Postconditioningmentioning
confidence: 99%